2008
DOI: 10.1007/s11259-008-9170-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistant Salmonella in dairy cattle in the United States

Abstract: Increased frequency of antimicrobial resistant Salmonella isolated from humans over the last quarter century in the United States has led to concern about the contribution animal production systems have played in the emergence and spread of antimicrobial resistant Salmonella. In order to better understand the potential role of dairy cattle as a reservoir for antimicrobial resistant Salmonella, it is important to understand methods currently used to measure the prevalence of antimicrobial resistance among Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 69 publications
2
33
0
Order By: Relevance
“…(64.3%) and E. coli (60%), also light resistance to cefixime, ciprofloxacin and ceftriaxone were determined. Other researchers reported the antibiotic resistance in enteric pathogens by other animal sources (6,14,19). Results of the current study showed that the overall rate of resistant Salmonella spp.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…(64.3%) and E. coli (60%), also light resistance to cefixime, ciprofloxacin and ceftriaxone were determined. Other researchers reported the antibiotic resistance in enteric pathogens by other animal sources (6,14,19). Results of the current study showed that the overall rate of resistant Salmonella spp.…”
Section: Discussionsupporting
confidence: 54%
“…It is clear that the gallbladder is an example of adaptation by the microorganism that Salmonella spp. are highly resistant to bile, which could be shedding slather process and contaminate the food product (5,6). Because of the aforementioned reports, a number of actions have been taken to reduce the prevalence of Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Thus dairy producers need to be aware that Salmonella can be found on their farms within apparently healthy cows, which is important in terms of food safety risks (Callaway et al, 2005). Using antimicrobial agents for cattle have been implicated as a source of human infection with antimicrobial resistant (AMR) Salmonella through direct contact with livestock and consumption of raw milk, meat and contaminated materials (Alexander et al, 2009). Antimicrobial resistant Salmonella are increasing due to the use of antimicrobial agents in food animals at subtherapeutic level or prophylactic doses for growth promotion and markedly increase the human health risks associated with consumption of contaminated milk and meat products (Endrias Zewdu and Cornelius 2009), through mutation, acquisition of resistance encoding genes (Fluit, 2005) and irrational use of antimicrobials in food animals (Fluit, 2005;Takele Beyene and Berihun Tesega, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Food borne illness associated with the consumption of foods has been reported in several places in Ethiopia and elsewhere (Estrada-Garcia et al, 2004;Chumber et al, 2007;Ghosh et al, 2007). Antimicrobial use in animal production systems has long been suspected to be the cause of emergence and dissemination of antimicrobial resistant Salmonella (Alexander et al, 2009).…”
Section: Introductionmentioning
confidence: 99%